О повышении эффективности получения кернов древесины для оценки характеристик древостоя - Anuchin A. S. (Innovative technologies in science and education, 2016)
improving the efficiency of obtaining wood cores for evaluating the characteristics of the stand is an important element of the preparatory work in the lumber camps. It was shown that the functional and technological analysis contributes to the development of new designs Buravov for these purposes.
Keywords: лесозаготовки; керн древесины; подготовительные работы; analysis of functional and technological; wood core; logging; preparatory work; функциональный анализ; технологический анализ